CALORIE INTAKE AND NUTRITIONAL STATUS AMONG STUDENTS 13-15 YEARS AT SMP NEGERI 2 TANJUNG PINANG - Aulia, Amanda; Meilani Kumala (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Nutritional status among adolescents is a global and national issue. Being overweight is a condition where a person's weight exceeds normal body weight, caused by excess fat accumulation. The impact of being overweight in adolescents will be a risk factor for degenerative diseases in young adulthood and old age. The study aimed to determine the distribution of nutritional status, daily caloric intake, and the relationship between caloric intake and nutritional status among adolescents. This study was conducted in an analytical observational manner with a cross-sectional design. This study was conducted at SMP Negeri 2 Tanjung Pinang to 262 grade IX students. Results: Most respondents were male (51.9%), aged 15 (58.8%). The nutritional status of most subjects was in the normal category (44.7%), with 30.5% being underweight and 24.8% overweight or obese. The study results showed a relationship between calorie intake and nutritional status in students aged 13-15, with a p-value = <0.001 using the Chi-Square Test.